2018
DOI: 10.21767/2321-547x.1000023
|View full text |Cite
|
Sign up to set email alerts
|

Artificial T Cell Mimetics to Combat Melanoma Tumor Growth

Abstract: Despite recent breakthroughs in melanoma treatment with anti-PD-1 immunotherapy, innovative approaches are needed to improve off-target effects. In this study, we report a T cell mimetic microparticle delivery of soluble PD1 aiming at providing a carrier substrate for future combinatorial and targeting efforts. Microparticles of sizes varying from (5 μm to-7 μm) were conjugated with soluble mouse or human PD-1 through nearly irreversible binding between streptavidin and biotin. PD-1 conjugated microparticles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Taking ad vantage of biomimetic materials, multiple immunosuppressive signals can be blocke Eventually, the immune tolerance of the TME is disrupted and the infiltration of immun cells increases. Mukundan et al reported a T cell mimic by constructing PD-1-conjugate microparticles (PDMPs) [21]. Unlike the antibody blockade, PDMPs could competitive In addition to directly killing tumor cells, T cell mimics could be fabricated as decoys to ameliorate immunosuppression and prevent excessive immune responses.…”
Section: T Cell Biomimetic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Taking ad vantage of biomimetic materials, multiple immunosuppressive signals can be blocke Eventually, the immune tolerance of the TME is disrupted and the infiltration of immun cells increases. Mukundan et al reported a T cell mimic by constructing PD-1-conjugate microparticles (PDMPs) [21]. Unlike the antibody blockade, PDMPs could competitive In addition to directly killing tumor cells, T cell mimics could be fabricated as decoys to ameliorate immunosuppression and prevent excessive immune responses.…”
Section: T Cell Biomimetic Strategymentioning
confidence: 99%
“…Eventually, the immune tolerance of the TME is disrupted and the infiltration of immune cells increases. Mukundan et al reported a T cell mimic by constructing PD-1-conjugated microparticles (PDMPs) [21]. Unlike the antibody blockade, PDMPs could competitively inhibit the PD-1/PD-L1 signaling, while maintaining normal immune tolerance and the CD45 + immune cell recruitment was enhanced with PDMPs treatment, which was a mechanism for tumor control.…”
Section: T Cell Biomimetic Strategymentioning
confidence: 99%
“…Mukundan et al have recently introduced a novel TCmimicking microparticle to combat PD1 signaling. [257] To this end, streptavidin-coated polystyrene microparticles with the size of 5-7 µm were conjugated with biotinylated human or mouse PD1 as a competitive inhibitory strategy with the PD1 on the surface of the TCs. In vivo studies showed that when a single dose of the particles was injected directly in the tumor (but not intravenously) of the melanoma-bearing animals, a 4.6-fold decrease in the tumor volume was observed in the group receiving the PD1-decorated particles.…”
Section: Artificial Immune Cells For Therapeutic Aimsmentioning
confidence: 99%